2022
DOI: 10.31603/mesi.6624
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and failure analysis of a diesel generator connecting rod

Abstract: This article reports a failure analysis of a diesel generator set connecting rod type 3516 B that has operated for 79,678 hours. From visual observation, connecting rod cylinder #10 has changed color in the shank area. This phenomenon may represent many cases of generator failure, so an analysis to identify the root cause of the failure is needed for scientific literature. In this case, fault tree analysis, SEM-EDX, chemical composition, and microstructure testing were performed to obtain more comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In case of fracture, dimples appear on the 45-degree shear lip. The ductile fracture form, resulting from the shear behavior, is elongated or C-shaped, and this parabolic shape may be characteristic of shear failure [11,14]. Figure 7(c) depicts a surface layer examination of the same area.…”
Section: Sem and Edx Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In case of fracture, dimples appear on the 45-degree shear lip. The ductile fracture form, resulting from the shear behavior, is elongated or C-shaped, and this parabolic shape may be characteristic of shear failure [11,14]. Figure 7(c) depicts a surface layer examination of the same area.…”
Section: Sem and Edx Analysismentioning
confidence: 99%
“…SEM analysis revealed that the piston core material was discolored due to heat, namely the formation of iron oxide. The level of heat experienced by the connecting rod was approximately 200 °C and EDX analysis suggested high levels of iron (Fe) and oxygen (O), confirming that the formation of iron oxide on the metal surface is caused by the influence of heat [11]. In [12], the authors adjusted the connecting rod structure.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Diesel engines have assumed a pivotal role across diverse sectors, including industrial, transportation, agriculture, marine, and heavy equipment domains. Renowned for their high power output, commendable fuel efficiency, and robust durability, diesel engines have become indispensable for various heavy-duty applications [13]. However, the indispensable nature of diesel engines has spurred concerted efforts to mitigate reliance on conventional diesel fuel.…”
Section: Introductionmentioning
confidence: 99%